Cardiac Gated Computed Tomography Used to Confirm Iatrogenic Aortic Valve Leaflet Perforation after Mitral Valve Replacement - Luke Oakley; Kathleen Love; Alfredo Ramirez; Gilbert Boswell; Keshav Nayak (Case Reports in Cardiology)
Aortic insufficiency from iatrogenic valve perforation from nonaortic valve operations is rarely reported despite the prevalence of these procedures. Rapid diagnosis of these defects is essential to prevent deterioration of cardiac function. In this paper, we describe a young man who reported to our institution after two open cardiac surgeries with new aortic regurgitation found to be due to an iatrogenic perforation of his noncoronary aortic valve cusp. This defect was not appreciated by previous intraoperative transesophageal echocardiography and was inadequately visualized on follow-up transthoracic and transesophageal echocardiograms. In contrast, cardiac gated computed tomography clearly visualized the defect and its surrounding structures. This case highlights the utility of cardiac gated computed tomography for cases of suspected valvular perforation when echocardiography is not readily available or inadequate imaging is obtained.